2001
DOI: 10.1051/0004-6361:20010505
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and molecular gas in the starburst galaxy NGC 4945

Abstract: Abstract. Spatial and kinematical correlations between the H i and12 CO(2−1) emission of the southern spiral galaxy NGC 4945 are studied with a common angular resolution of ∼23 (corresponding to 750 pc at D = 6.7 Mpc) and a velocity resolution of ∼7 km s −1 . The 1.4 GHz continuum emission is also observed. The H i kinematics yield a galaxy mass of ∼1.4×1011 M within radius R = 380 , with molecular and neutral atomic gas each contributing ∼2%, respectively. A central continuum source of size 7 . 6 × 3 . 4 (250… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
61
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 39 publications
21
61
0
Order By: Relevance
“…The total area of line emission is 1.5 times the naturally-weighted beam area (8.6 times the uniformly-weighted beam area), or 4500 pc 2 . The H91α + H92α spectrum integrated over the line emitting region shows a strong line detection with significance of 52σ, with centroid at 581 km s −1 in good agreement with the CO systemic velocity of 585 km s −1 (Chou et al 2007) and with the velocity of the HI absorption towards the nucleus of 585 km s −1 , though significantly higher than the HI systemic velocity inferred from the whole galaxy of 557 km s −1 (Ott et al 2001). The line FWHM is 220 km s −1 after deconvolving the instrumental velocity resolution of 42 km s −1 .…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The total area of line emission is 1.5 times the naturally-weighted beam area (8.6 times the uniformly-weighted beam area), or 4500 pc 2 . The H91α + H92α spectrum integrated over the line emitting region shows a strong line detection with significance of 52σ, with centroid at 581 km s −1 in good agreement with the CO systemic velocity of 585 km s −1 (Chou et al 2007) and with the velocity of the HI absorption towards the nucleus of 585 km s −1 , though significantly higher than the HI systemic velocity inferred from the whole galaxy of 557 km s −1 (Ott et al 2001). The line FWHM is 220 km s −1 after deconvolving the instrumental velocity resolution of 42 km s −1 .…”
Section: Resultssupporting
confidence: 64%
“…This was seen also in CO(2−1) by Ott et al (2001) with SEST at 23 resolution. However, inflow was not seen in the H91α + H92α dynamics within 4 of the nucleus.…”
Section: Comparison With Literaturesupporting
confidence: 52%
See 2 more Smart Citations
“…Madejski et al (2000) and Done et al (2003) suggested that the megamaser spots are aligned with the absorbing disk/torus at 0.1-1 pc. In addition to this dense absorbing disk, the nucleus is completely embedded in a column of ∼10 23 cm −2 at ∼25 pc, which may be due to a bar-driven gas inflow (Ott et al 2001) or perhaps a high-latitude extension of the disk/torus. The extreme absorption region is surrounded by an extended, dusty, lower absorption region on scales of 50-100 pc in the starburst region.…”
Section: Introductionmentioning
confidence: 99%